Kharaj dan Jizyah: Instrumen Fiskal Klasik Islam dan Relevansinya di Era Modern: Kharaj and Jizyah: Classic Islamic Fiscal Instruments and Their Relevance in the Modern Era - Laita Nantian; Pinky Dewi Sukesi Putri; Chantyka Rahma Putri Nadyanti; Veronica Arshanda; Amalia Nuril Hidayati (TIJARAH: Jurnal Ekonomi, Manajemen, dan Bisnis Syariah, 2025)
Kharaj and jizyah are instruments that played a significant role in public financing and the creation of distributive justice during the era of classical Islamic governance. However, the values derived from kharaj and jizyah remain relevant to the implementation of fiscal policy in the modern era. This study aims to examine the economic and social functions of kharaj and the principles of justice in jizyah, compare them with modern taxation systems, and analyze their relevance in developing fiscal policies based on maqāṣid al-sharī‘ah. This research employs a literature study method by reviewing secondary sources such as books, academic journals, scholarly articles, and relevant regulations. The findings indicate that although the literal application of kharaj and jizyah faces legal and pluralistic challenges in the contemporary context, their moral values; such as distributive justice, resource productivity, and reciprocal obligations, remain relevant as ethical foundations for fiscal policy. These values may be integrated through reforms in land taxation, natural resource taxation, and universal social contribution schemes to realize a modern fiscal system that is more just, transparent, and oriented toward social welfare.